On the Choice of Numeraire and Certainty Price in General Equilibrium Models of Price Uncertainty - Flemming, John S.; Turnovsky, Stephen J.; Kemp, Murray C. (Review of Economic Studies, 1977)
John S. Flemming, Stephen J. Turnovsky, Murray C. Kemp; On the Choice of Numeraire and Certainty Price in General Equilibrium Models of Price Uncertainty,